2020
DOI: 10.3389/fimmu.2020.00789
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Based Immunoengineered Approaches for Combating HIV

Abstract: Highly active antiretroviral therapy (HAART) serves as an effective strategy to combat HIV infections by suppressing viral replication in patients with HIV/AIDS. However, HAART does not provide HIV/AIDS patients with a sterilizing or functional cure, and introduces several deleterious comorbidities. Moreover, the virus is able to persist within latent reservoirs, both undetected by the immune system and unaffected by HAART, increasing the risk of a viral rebound. The field of immunoengineering, which utilizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 106 publications
2
10
0
1
Order By: Relevance
“…A great variety of works are investigating new means and bioengineering techniques to deliver drugs to infected cells and/or present immunogens to immune cells in specific compartments, which could lead to enhanced efficiency of natural immune responses [ 181 , 182 , 183 , 184 , 185 , 186 ]. Pino et al demonstrated in SIV-infected RM that administration of FTY720 (fingolimod), a drug used to treat multiple sclerosis, limits viral persistence by increasing the number of cytolytic cells in the LN, a critical site for HIV/SIV replication and persistence [ 187 ].…”
Section: Evaluation Of Hiv Cure Strategies With the Help Of Nhp Modelsmentioning
confidence: 99%
“…A great variety of works are investigating new means and bioengineering techniques to deliver drugs to infected cells and/or present immunogens to immune cells in specific compartments, which could lead to enhanced efficiency of natural immune responses [ 181 , 182 , 183 , 184 , 185 , 186 ]. Pino et al demonstrated in SIV-infected RM that administration of FTY720 (fingolimod), a drug used to treat multiple sclerosis, limits viral persistence by increasing the number of cytolytic cells in the LN, a critical site for HIV/SIV replication and persistence [ 187 ].…”
Section: Evaluation Of Hiv Cure Strategies With the Help Of Nhp Modelsmentioning
confidence: 99%
“…Additionally, they can be sorted out in either neutralizing antibodies (Nabs) or no neutralizing antibodies (Non-Nabs). The action of the first ones is directed at blocking infection by binding to the envelope of free viruses, while the other is toward recognition of the envelope during virus entry or on the surface of infected cells [ 136 , 137 ].…”
Section: Nanotechnology Approaches For Hiv/aids Treatmentmentioning
confidence: 99%
“…In addition, NPs significantly reduced the RNA and protein expression of HIV-1 [ 94 ]. On the other hand, current CRISPR-Cas9 delivery techniques use electroporation to facilitate DNA entry into living cells, which is difficult to control and can generate cytotoxicity [ 137 ]. Shahbazi et al showed how the use of AuNPs can mediate CRISPR-Cas9 components to target cells with higher efficiency and lower cytotoxicity [ 160 ].…”
Section: Nanotechnology Approaches For Hiv/aids Treatmentmentioning
confidence: 99%
“…According to a recent study, significant active therapeutics for HIV treatment defined the status of AgNPs as a known HIV antiagent in the initial phase of viral duplication and later stages of the HIV life cycle [8]. Additionally, Ag and Au's metals have demonstrated excellent biocompatibility, optical properties, high surface area to volume ratio, and excellent conductivity [9].…”
Section: Introductionmentioning
confidence: 99%